PENYIMPANGAN MAKNA DAN PERUBAHAN KONSTITUEN DALAM HUMOR CAK LONTONG - Sukardi, Mochamad Ighfir; Yuwana, Rawuh Yuda; Sumarlam, Sumarlam (Sunan Kalijaga State Islamic University Yogyakarta, 2016)
The purposes of this research are (1) to describe the deviation of meaning in Cak Lontong’s humor materials (2) to describe the changing of constituent in Cak Lontong’s humor materials. This research is a descriptive-qualitative research. Listening method is used as the data collecting technique, using technique of tap and write. The data analysis method is the reference equalization, using comparative technique to support codification, reduction, presentation, and interpretation. The results of this research are: Cak Lontong exploits gaps and possibilities of new meanings that can be used in words; Cak Lontong deviates meanings by establishing the second meaning as an effort to give surprise to his listeners; and Cak Lontong exploits figurative words of homonymy, e.g. “mengarungi” and “ngurusi” to play the meanings that are conveyed in using the language. The power of Cak Lontong’s humor is in the sensitivity in finding gaps of words, then presenting them by trapping listener’s interpretation to the unintended meanings. A changing constituent occurs to function of process to be participant, participant to participant, participant to circumstances, and circumstances to circumstances. It changes meanings and interpretations of a same word.